PERWATAKAN TOKOH DALAM NOVEL GENDUK KARYA SUNDARI MARDJUKI - Yuliana, Yuliana; Salem, Laurensius; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study describes the problem, while this research is useful for researchers to increase knowledge and insight in analyzing the works of literature, can be used by teachers and students as a medium of learning and as a comparison material for other research.